The invisible world : early modern philosophy and the invention of the microscope - Wilson, Catherine, 1951- (Princeton, N.J. : Princeton University Press, 1995)
Wilson argues that the discovery of the microworld - and the apparent role of living animalcula in generation, contagion, and disease - presented metaphysicians with the task of reconciling the ubiquity of life with human-centered theological systems. It was also a source of problems for philosophers concerned with essences, qualities, and the limits of human knowledge, whose positions are echoed in current debates about realism and instrument-mediated knowledge. Covering the contributions of pioneering microscopists (Leeuwenhoek, Swammerdam, Malpighi, Grew, and Hooke) and the work of philosophers interested in the microworld (Bacon, Descartes, Leibniz, Malebranche, Locke, and Berkeley), she challenges historians who view the abstract sciences as the sole catalyst of the Scientific Revolution as she stresses the importance of observational and experimental science to the modern intellect.
In the seventeenth century the microscope opened up a new world of observation, and, according to Catherine Wilson, profoundly revised the thinking of scientists and philosophers alike. The interior of nature, once closed off to both sympathetic intuition and direct perception, was now accessible with the help of optical instruments. The microscope led to a conception of science as an objective, procedure-driven mode of inquiry and renewed interest in atomism and mechanism. Focusing on the earliest forays into microscopical research, from 1620 to 1720, this book provides us with both a compelling technological history and a lively assessment of the new knowledge that helped launch philosophy into the modern era.
1. Science and Protoscience -- 2. The Subtlety of Nature -- 3. Instruments and Applications -- 4. Preexistent and Emergent Form -- 5. Animalcula and the Theory of Animate Contagion -- 6. The Philosophers and the Microscope -- 7. The Microscope Superfluous and Uncertain -- 8. Truths and Appearances.
Includes bibliographical references (pages 257-272) and index.
Print version record.
JSTOR
Keywords: Philosophy and science -- Europe -- History -- 17th century; Philosophy, Modern -- 17th century; Microscopes -- Europe -- History -- 17th century; Europe -- Intellectual life -- 17th century; Philosophy and science; Microscopes; Philosophy, Modern; Philosophy -- history; Microscopy -- history; Philosophie et sciences; Philosophie -- 17e siècle.; Microscopes; Europe -- Vie intellectuelle -- 17e siècle.; Philosophie et sciences -- Europe -- Histoire -- 17e siècle.; Microscopes -- Europe -- Histoire -- 17e siècle.; SCIENCE -- History; Intellectual life; Microscopes; Philosophy and science; Philosophy, Modern; Europe; Philosophie; Naturwissenschaften; Filosofie; Microscopie; Europe -- Intellectual life -- 17th century; Science -- Europe -- History -- 17th century; Science -- Philosophy; Philosophy, Modern -- 17th century; Microscopy -- Europe -- 17th century; Philosophie -- 17e siècle.; Philosophie et sciences -- Europe -- 17e siècle.; Microscopes -- Europe -- 17e siècle.; Philosophie des sciences; Europe -- Vie intellectuelle -- 17e siècle.; 1600-1699; History